United Arab Emirates : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Issues and statistical appendices are discussed. Government-related entities (GREs) have been a major source of growth and development for the United Arab Emirates (U.A.E.) economy. The global financial and economic crisis has, however, unveiled the fiscal and financial risks posed by GREs. The objective of this paper is to identify the risks posed by financially underperforming GREs. Policies to manage GREs are also explained, and policy responses to crisis are explained. Statistical appendices are included.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet